Functional Analysis of Forkhead Transcription Factor Fd59a in the Spermatogenesis of Drosophila melanogaster. - Tang, T.; Pei, M.; Xiao, Y.; Deng, Y.; Lu, Y.; Yu, X.Q.; Wen, L.; Hu, Q. (Insects, 2024)
Spermatogenesis is critical for insect reproduction and is regulated by many different genes. In this study, we found that Forkhead transcription factor Fd59a functions as a key factor in the spermatogenesis of Drosophila melanogaster. Fd59a contains a conversed Forkhead domain, and it is clustered to the FoxD subfamily with other FoxD members from some insect and vertebrate species. Mutations in Fd59a caused swelling in the apical region of the testis. More importantly, fewer mature sperm were present in the seminal vesicle of Fd59a mutant flies compared to the control flies, and the fertility of Fd59a[2/2] mutant males was significantly lower than that of the control flies. Immunofluorescence staining showed that the homeostasis of the testis stem cell niche in Fd59a[2/2] mutant and Fd59a RNAi flies was disrupted and the apoptosis of sperm bundles was increased. Furthermore, results from RNA sequencing and qRT-PCR suggested that Fd59a can regulate the expression of genes related to reproductive process and cell death. Taken together, our results indicated that Fd59a plays a key role in the spermatogenesis of Drosophila.